The Multimodal transport and its impact on Ecuadorian legislation - Piloso Moreira, Verónica Alexandra (SATHIRI, 2019)
The legal framework of multimodal transport configures participants in this legal commercial act called multimodal transport contract. Despite the commercial usefulness of this activity, it does not have uniform regulations to respond to the various legal approaches that arise from the conclusion of the multimodal transport contract. In this sense the contractual elements evolve according to the norms that regulate multimodal transport, posing indirect solutions to many specific cases that originate from the commercialization of goods and that can"™t be solved in an efficient way. There are international organizations that have made contributions, among these MERCOSUR, the Andean Community of Nations, developing regulatory instruments that regulate transportation and include penalties for non-compliance; in the same way as the United Nations, but are still insufficient. The studies carried out show that there is a very weak international standard when resolving conflicts resulting from this activity. As a result, with Ecuador, only the Organic Code of production of trade and investment and its Regulation of the Customs Facilitation where it establishes the multimodal transport as a customs operation and in the corresponding to the national regime in multimodal transport, due to the necessity of transportation , Has been growing so it is necessary to carry out an in-depth study regarding the national and international regulations of multimodal transport to propose solutions that allow the growth of activity, which is the contribution of this work.
Keywords: multimodal transport; contract; multimodal transport operator; international organizations; consignee; dispatcher; carrier